2019
DOI: 10.1016/j.sjbs.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

A Study on actinobacterial diversity of Hampoeil cave and screening of their biological activities

Abstract: Caves are oligotrophic, dark and less-explored environments and are considered as sources of promising microbial strains in biotechnology. Hampoeil Cave is located in massive dolomite with thin bedded limestone in northwestern of Iran. In an isolation and screening program, various samples from soil, water, floor, wall and ceiling of Hampoeil cave and its invertebrates were collected. Four various treatments and 10 different isolation media were used for the isolation of the actinobacteria. Screening of the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 32 publications
2
21
0
1
Order By: Relevance
“…From the cultivated isolates, it showed a dominance of Streptomyces genera which comprised 76% of the total number of isolates. Recent reports on actinobacteria from limestone niches have also shown Streptomyces to be the dominant genera 8,13,44,45 . A number of novel actinobacterial strains have also been reported from other limestone niches.…”
Section: Diversity Of Actinobacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…From the cultivated isolates, it showed a dominance of Streptomyces genera which comprised 76% of the total number of isolates. Recent reports on actinobacteria from limestone niches have also shown Streptomyces to be the dominant genera 8,13,44,45 . A number of novel actinobacterial strains have also been reported from other limestone niches.…”
Section: Diversity Of Actinobacteriamentioning
confidence: 99%
“…Limestone-rich areas mainly dominated by a CaCO 3 environment, are under-explored ecological niches for mining of microorganisms for various metabolic properties. Recent studies have revealed that both hypogean and epigean limestone actinobacteria are potential antibiotics producers [8][9][10][11][12][13][14] . The state of Meghalaya located in the north-eastern part of India falls under the Indo-Burma Biodiversity Hotspot 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We are aware that limestone areas similar to Boho have long been regarded as a rich source of antibiotic producing Streptomyces [43][44][45] [34]. Finally, a gene cluster from Streptomyces isolates McG7 and McG8 showed similarity to those previously identified for the synthesis of cyslabdan, an antimicrobial potentiator [33].…”
Section: Discussionmentioning
confidence: 95%
“…Digging deeper, research has shown that moonmilk contains an abundance of Streptomyces that have antibacterial activity against a wide range of bacteria and fungi [49,50], and display strong growth suppression against multi-resistant Rasamsonia argillacea, a causative agent of invasive mycosis in cystic fibrosis and chronic granulomatous diseases [50]. Similar studies from the Hampoeil cave (dolomite with limestone) in Iran, linked to Palaeolithic habitation, revealed many antimicrobialproducing Streptomyces, as well as other species [51].…”
Section: Antibiotics From Cavesmentioning
confidence: 97%